Critical role of a pre-purge setup in the thermal desorption analysis of volatile organic compounds by gas chromatography with mass spectrometry - Kim, Yong-Hyun; Kim, Ki-Hyun (Journal of separation science, 2015)
In general, volatile organic compounds in ambient air are quantified by following a well‐defined standard calibration procedure using a gas‐/liquid‐phase standard. If the liquid standard is analyzed by a thermal desorption, the solvent effect is unavoidable through the alteration of breakthrough properties or retention times. To learn more about the variables of the thermal desorption‐based analysis, the effect of pre‐purge conditions was evaluated for 18 volatile organic compounds with different types of sorbent tube materials by fixing standard volume (1 μL) and flow rate (100 mL/min). The gas phase calibration was also carried out as reference for the non‐solvent effect. A single tube filled with Tenax TA exhibited the least solvent effect with the short pre‐purge (1 min), while being subject to the breakthrough at or above 10 min pre‐purge. For a three‐bed sorbent tube with Carboxen 1000, at least 10 min of pre‐purge was needed for the compounds with a retention time close to methanol (e.g., propanal). Another three‐bed tube with Carbopack X reduced the solvent effect efficiently for a short pre‐purge (2 min) without the breakthrough. As such, the solvent effect can be adjusted by the proper control of the sorbent tube application.